Creating and sustaining a collaborative mentorship team : a handbook for practice and research - Gut, Dianne Marie; Beam, Pam; VanDerveer, Beth J.; Trube, Barbara (Perspectives in mentoring., 2020)
"In response to changes in the workforce, scholars are calling for mentoring that is more fluid, flexible, and responsive to the needs of diverse groups of individuals, whether culturally (Kochan & Pascarelli, 2012; Kochan, Searby, George, & Mitchell Edge, 2015) or intergenerationally (Thorpe, 2012) diverse. With these changes, there is a greater demand for intergenerational and intercultural collaboration and mentoring. One response to these changes is to take a more collaborative, interactive, and transformational approach to mentoring. In response, this book provides a model for collaborative mentoring, based on best-practice, grounded in theory and research, and framed by our Dynamic Model of Collaborative Mentoring. Each chapter provides a description of one of the five components of the mentoring model which are grounded in theory and include: agency, values, engagement, patterns, and roles. Individual chapters provide resources, prompts and questions to guide reflection, and suggested readings. This book is authored by four individuals who work, research, and write as a team. The book itself is the product of our mentoring research as well as our mentoring practice in action. It is current and timely, focusing on a team process which is collaborative, dynamic, reflective, and constantly developing and evolving"--